Integration of Remote Usability Tests in eXtreme Programming: A Literature Review - Sánchez-Hernández, Diego (2020)
This study is intended to answer the question of how to integrate remote usability tests into eXtreme Programming. The study is based on a literature review involving search, selection and results classification. Keywords, emerging categories, and search strings in relevant databases were used. An analysis of the current state of the components and processes that have been used in this type of integration has led to a combined approach in areas such as: 1. Requirements management, 2. Management of team members including developers, usability evaluators, experts and final users, 3. Management of tests, data collected and feedback, 4. Design, and 5. Activities carried out within an iteration. It is concluded that more research, experimentation and documentation are necessary to be able to recommend integration processes that satisfy demands and take advantage of eXtreme Programming and remote usability tests. Finally, it is necessary to confront the challenges posed by the difference in the holistic visions of both approaches, as well as communication problems between usability developers and evaluators, adaptation of eXtreme components, and the limited priority assigned to usability efforts.